Interaction of peripheral nerves and mast cells, eosinophils, and basophils in the development of pruritus. Issue 12 (29th October 2019) - Nakashima, Chisa; Ishida, Yoshihiro; Kitoh, Akihiko; Otsuka, Atsushi; Kabashima, Kenji
Abstract: Mast cells, eosinophils and basophils are central effector immune cells in allergic skin inflammation including atopic dermatitis (AD). Recent studies revealed that the bidirectional interaction between these three immune cell types (mast cells, eosinophils and basophils) and the nervous system is involved in the pathogenesis of neurogenic inflammation, pain and pruritus. Emerging evidence shows that these cells are the main source of pruritogens such as histamine, neuropeptides and cytokines, which are potential new therapeutic targets for drug development in chronic pruritus. For instance, many Th2 cytokines including interleukin (IL)‐4, 13 and 31 have been recognized as some of the most promising targets for the treatment of chronic pruritus in AD. In this review, we highlight the link between these three immune cell subsets and peripheral nerves, with emphasis on the development of chronic pruritus such as AD. We present cytokines and receptors of these three immune cells and peripheral nerves, and discuss the therapeutic potential of targeting these neuro‐immunological processes.